Natural Language Interfaces to Databases for English vs. Hindi: The Research Gap - Harjit Singh, (Design Engineering, 2021)
Accessing a database requires the knowledge of Structured Query Language (SQL). It is not easy for end users to learn SQL. A Natural Language Interface to Database (NLIDB) allows the end users to access databases in a natural language. Some NLIDB systems have been developed for Hindi. But there exists the research gap in the development of those systems as compared to the systems developed for English. Very limited research has been done to develop NLIDB systems for Hindi as compared to English. This paper analyses the systems developed for both these languages. It compares the existing systems and explores the challenges to NLIDB development for Indian languages including Hindi. The paper discusses the future research directions to fulfill the research gap in the development of NLIDB systems for Hindi and other Indian languages.